Progress of nanoparticle drug delivery system for the treatment of glioma - Lai, Guogang; Wu, Hao; Yang, Kaixia; Hu, Kaikai; Zhou, Yan; Chen, Xiao; Fu, Fan; Li, Jiayi; Xie, Guomin; Wang, Hai-Feng; Lv, Zhongyue; Wu, Xiping (Frontiers in Bioengineering and Biotechnology, 2024)
Gliomas are typical malignant brain tumours affecting a wide population worldwide. Operation, as the common treatment for gliomas, is always accompanied by postoperative drug chemotherapy, but cannot cure patients. The main challenges are chemotherapeutic drugs have low blood-brain barrier passage rate and a lot of serious adverse effects, meanwhile, they have difficulty targeting glioma issues. Nowadays, the emergence of nanoparticles (NPs) drug delivery systems (NDDS) has provided a new promising approach for the treatment of gliomas owing to their excellent biodegradability, high stability, good biocompatibility, low toxicity, and minimal adverse effects. Herein, we reviewed the types and delivery mechanisms of NPs currently used in gliomas, including passive and active brain targeting drug delivery. In particular, we primarily focused on various hopeful types of NPs (such as liposome, chitosan, ferritin, graphene oxide, silica nanoparticle, nanogel, neutrophil, and adeno-associated virus), and discussed their advantages, disadvantages, and progress in preclinical trials. Moreover, we outlined the clinical trials of NPs applied in gliomas. According to this review, we provide an outlook of the prospects of NDDS for treating gliomas and summarise some methods that can enhance the targeting specificity and safety of NPs, like surface modification and conjugating ligands and peptides. Although there are still some limitations of these NPs, NDDS will offer the potential for curing glioma patients.